Using mobile health apps during the Covid-19 pandemic in a developing country for business sustainability - Hazem Rasheed Gaber; Lamiaa Mostafa Hassan (Cogent Business & Management, 2022)
With the outbreak of the Covid-19 pandemic, many health providers and insurance companies have faced challenges due to the high levels of uncertainty. Many of these companies have relied on mobile apps to connect with their patients and clients to ensure business sustainability during and after the pandemic. This paper examines the factors that affect the intention of the actual users of these apps to continue using them during the pandemic. Given the novelty of the adoption of these apps in developing countries and the scarcity of research investigating users' relationships with them, this research was conducted on users of mobile health apps in Egypt, which has witnessed a massive growth in the penetration of smartphones. A conceptual framework was developed based on an extensive literature review and revisiting the technology acceptance model (TAM) and the expectation-confirmation model (ECM). An online survey was used to collect the data from 442 actual users of mobile health apps in Egypt. The data were analyzed using partial least square structural equation modeling through SMART PLS 3.0. The main findings showed that continuance intention is affected by satisfaction, perceived usefulness, perceived ease of use, and attitudes. The paper contributes theoretically by introducing a multi-theoretical framework that explains users' intentions to use mobile health apps. Furthermore, it provides guidelines for healthcare providers and insurance companies when using these apps to ensure business sustainability.
Keywords: 650; business sustainability; continuance intention; Covid-19; expectation-confirmation model; health care industry; mobile apps; technology acceptance model